DUAL ROLE OF LEMNA MINOR IN NUTRIENT REMEDIATION AND GROWTH PERFORMANCE OF OREOCHROMIS NILOTICUS IN INTENSIVE TANK SYSTEMS - Marinus, E.; Emefe, O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study evaluated the dual role of Lemna minor as a phytoremediator and supplementary feed for Oreochromis niloticus under controlled tank conditions. The experiment lasted 12 weeks; it was performed with four treatment groups: commercial feed as a control, partial replacement of the feed with duckweed, full feed and duckweed, and duckweed-only. The results showed significant improvements in water quality with more duckweed added. There were reductions in ammonia (from 0.4234 to 0.0372 mg/L), nitrate (from 4.712 to 1.231 mg/L), and nitrite (from 0.09278 to 0.01722 mg/L), along with increased dissolved oxygen levels (from 4.219 to 5.941 mg/L). Nevertheless, there was a lower growth performance when the duckweed was fully substituting other feed and with SGR decreasing from 4.08% day⁻¹ in the control to 1.81% day⁻¹ in the duckweed-only treatment.” The partially inclusive treatments were characterized by good compromise between good growth and improved environmental conditions. The research demonstrates that Lemna minor can be a valuable component of the combined aquaculture systems, enhancing water quality and ensuring moderate fish growth. As it is recommended, duckweed meal is to be added to the regular feed, but not as a sole diet to maximize productivity and sustainability.